2014
DOI: 10.3382/ps.2013-03819
|View full text |Cite
|
Sign up to set email alerts
|

Dietary threonine requirement of Pekin ducks from 15 to 35 days of age based on performance, yield, serum natural antibodies, and intestinal mucin secretion

Abstract: A study was conducted to establish the dietary Thr requirement of Pekin ducks from 15 to 35 d of age. Experimental diets were formulated to contain 0.55, 0.60, 0.65, 0.75, and 0.85% Thr (0.57, 0.60, 0.64, 0.72, and 0.80% on an analyzed basis) and were studied in 2 experiments. In experiment 1, each diet was fed to 10 pens of 52 drakes per pen. Samples were collected at d 35 for determinations of carcass yields, serum immune parameters, and intestinal characteristics. Experiment 2 was a digestibility study, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…These results were in line with Guo ( 2011 ), who reported the optimal Met requirements for maximum feather weight were 0.476%, and for 1,000 down weight and down length were 0.482 and 0.485%, respectively, from 1 to 21 d. Zhang et al. ( 2014 ) reported that the fourth primary wing feather was significantly shorter in birds fed 0.57% Thr diet showing that only a severe deficiency of Thr reduced the feather growth of Pekin ducks from 15 to 35 d age. Similarly, the fourth primary feather length was significantly shorter in birds fed 0.30% Met of diet based on the results presented herein, indicating that a deficiency of Met can lead to impaired feather growth of Pekin ducks.…”
Section: Discussionsupporting
confidence: 87%
“…These results were in line with Guo ( 2011 ), who reported the optimal Met requirements for maximum feather weight were 0.476%, and for 1,000 down weight and down length were 0.482 and 0.485%, respectively, from 1 to 21 d. Zhang et al. ( 2014 ) reported that the fourth primary wing feather was significantly shorter in birds fed 0.57% Thr diet showing that only a severe deficiency of Thr reduced the feather growth of Pekin ducks from 15 to 35 d age. Similarly, the fourth primary feather length was significantly shorter in birds fed 0.30% Met of diet based on the results presented herein, indicating that a deficiency of Met can lead to impaired feather growth of Pekin ducks.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, recent studies by Azzam et al [16,17] detected significant improvements in egg production when the Thr level increased from 0.47% to 0.67% from 40 to 48 wk of age, while increasing the Thr level from 0.57% to 0.74% from 56 to 64 wk improved egg production and the egg mass in laying hens. In laying quails, egg production, the egg weight, and FCR were improved by increasing the Thr concentration in the diet [25] Similar findings have been obtained in meat-type birds, including turkey toms [5], Japanese quails [6], and Pekin ducks from 1 to 21 days of age [8] and from 15 to 35 days of age [9], where the average daily weight gain and FCR increased significantly with the dietary Thr concentration. Furthermore, in chickens challenged with infectious bursal disease, the body weight gain and FCR were improved significantly by increasing the Thr concentration in the diet [7].…”
Section: Resultsmentioning
confidence: 63%
“…Thr is essential for mucin production, which plays a major role in intestinal health and nutrient absorption [2], as well as for the production of antibodies [3] and feather development [4]. In poultry, Thr deficiency has negative effects on the growth performance, carcass yield, and quality by reducing the thigh and breast yield, increasing body fat deposition, inhibiting feather development, and decreasing antibody formation, as well as having positive effects on the mortality rate [59]. In broiler chickens and quails, increasing the Thr levels during embryonic development improves the growth performance, mucin secretion, and the humoral immune response after hatching and feeding the supplemented diet [1012].…”
Section: Introductionmentioning
confidence: 99%
“…(2009), Jiang et al (2017 who reported that the growth performance was enhanced when dietary supplementation with Thr in ducks. In addition, Zhang et al (2014) detected the Thr requirement of Pekin ducks from 15 to 35 d of age, and reported that the average daily weight gain increased significantly with the dietary Thr concentration. Bi et al (2012) conducted an experiment on Pekin ducks from hatch to 21 d with graded concentration of Thr in diets and reported significant improvement with increased dietary Thr levels.…”
Section: Discussionmentioning
confidence: 99%